The Harmonics Effect of Variable Speed Drives on Generator Performance - Mardiyanto, Ignatius Riyadi (Bandung State Polytechnic (Politeknik Negeri Bandung), 2020)
Large motors often burden synchronous generators as power plants in factories. This motor is commonly using to regulate rotation using Variable Speed Drive (VSD). From the load side, VSD, as a regulator of motor rotation, can reduce power loss. On the generator side as a power plant, this load with VSD affects the waveform of the generator. The experiments on a small capacity generator (6 kVA) with a VSD as regulating the motor rotation with a load of about 1.1 kW shows effectiveness power transfer is about 40.7% with VSD, and without VSD, efficiency is approximately 39.6%. The motor losses by installing VSD interpreted as transferring losses to the generator with savings is about 1 %. The experiments also showed that generator performance decreases when loaded with VSD at around 6%, and a generator temperature increases at 20 0C higher than without VSD.